Salmonella in retail food and wild birds in Singapore — prevalence, antimicrobial resistance, and sequence types - Aung, Kyaw Thu (2020)
Non-typhoidal salmonellosis is a leading cause of foodborne zoonosis. To better understand the epidemiology of human salmonellosis, this study aimed to determine the prevalence, antimicrobial resistance and sequence types of Salmonella in retail food and wild birds (proximity to humans) in Singapore. We analyzed 21,428 cooked and ready-to-eat food and 1,510 residual faecal samples of wild birds collected during 2010-2015. Thirty-two Salmonella isolates from food and wild birds were subjected to disc diffusion and multi-locus sequence typing (MLST). Salmonella was isolated from 0.08% (17/21,428) of food and 0.99% (15/1510) of wild birds. None of the isolates from wild birds (n = 15) exhibited phenotypic resistance, while the isolates from food (47.1%, 8/17) showed a high prevalence of phenotypic resistance to, at least, one antimicrobial. These findings suggested that the avian Salmonella isolates had been subjected to less antimicrobial selection pressure than those from food samples. MLST revealed specific sequence types found in both food and wild birds. The study can guide future studies with whole-genome analysis on a larger number of isolates from various sectors for public health measures.